First report of Sarcocystis halieti in Asia: the genetic confirmation in muscles of the Eurasian sparrowhawk (Accipiter nisus) from Iran - Sazmand, Alireza; Moradi, Leili; Almasi, Pardis; Nabavi, Reza; Prakas, Petras (Scientific reports, 2025)
Previous studies showed that the Eurasian sparrowhawk Accipiter nisus (Linnaeus, 1758) acts as the definitive host of the Sarcocystis halieti (Apicomplexa: Sarcocystidae) Gjerde, Vikøren et Hamnes, 2017. Herein, we report macrocysts of S. halieti in the pectoral muscle of a Sparrowhawk in the west of Iran. Between September 2019 and December 2023, a total of 55 wild birds belonging to 8 orders, 9 families, 18 genera, and 21 species were examined in Hamedan province, western Iran. In one Eurasian sparrowhawk, macroscopic cysts resembling rice grains were observed in the breast muscle of the bird. None of the other examined birds were infested with macrosarcocysts. DNA extracted from sarcocysts was molecularly characterized at four nuclear and mitochondrial DNA markers (the 18 S rRNA, 28 S rRNA, cox 1 genes, and the ITS1 region). Sequence analysis confirmed the identity of the macrosarcocysts as Sarcocystis halieti . This is the first report of S. halieti in Asia. Sparrowhawk proved to act as both the definitive and intermediate host of Sarcocystis halieti. The phenomenon of the same species of Sarcocystis serving as both hosts is extremely rare among birds and needs to be studied further.